2016
DOI: 10.1177/1049731514563988
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Modular Research-Supported Treatment in Child Welfare

Abstract: Objective: Increasing rates of mental health needs in child welfare clients highlight the importance of training child welfare workers in effective mental health interventions. This pilot study evaluates the effects of training public child welfare workers and interns in modularized research-supported treatments (RSTs). Methods: We compared knowledge of and attitudes toward RSTs and barriers and facilitators to their use in a sample of 26 field instructors and 11 master of social work students trained in modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Although the interventions described have varying levels of evidence, we recognise that CW practitioners, like all child-serving professionals, are being called to be more evidenced based. We see evidence, from our work in the field (Schuler et al, 2016) and other studies (e.g. Aarons and Palinkas, 2007;James et al, 2015;Leathers et al, 2016), that professionals engaged in advancing child well-being are open to implementing evidence-based practices.…”
Section: Discussionmentioning
confidence: 60%
“…Although the interventions described have varying levels of evidence, we recognise that CW practitioners, like all child-serving professionals, are being called to be more evidenced based. We see evidence, from our work in the field (Schuler et al, 2016) and other studies (e.g. Aarons and Palinkas, 2007;James et al, 2015;Leathers et al, 2016), that professionals engaged in advancing child well-being are open to implementing evidence-based practices.…”
Section: Discussionmentioning
confidence: 60%
“…Theory and methods used to study dissemination EBP in mental health services can be applied to research on EBP in child protection. Efforts by Fitzgerald et al (2015) and Schuler et al (2016) to train child protection workers to work with manageable components of EBP were influenced by work by clinical psychologists distilling common elements across related treatment ESIs into “practice elements” (e.g., cognitive reframing for depression and anxiety; Chorpita, Daleiden, & Weisz, 2005; see also Barth et al, 2012; Weisz et al, 2012). Kolko et al (2012) suggested two new directions in research in child protection on the basis of previous research in psychology.…”
Section: Child Well-beingmentioning
confidence: 99%
“…protection toward the growing evidence base on best practice (e.g., California Child Welfare Co-investment Partnership, 2014). They could also advocate for using Medicaid to pay for designated ESIs for children and their families, which is currently done by some, but not all, states (Smith, Granja, Ekono, Robbins, & Nagarur, 2016) Fitzgerald et al (2015) and Schuler et al (2016) to train child protection workers to work with manageable components of EBP were influenced by work by clinical psychologists distilling common elements across related treatment ESIs into "practice elements" (e.g., cognitive reframing for depression and anxiety; Chorpita, Daleiden, & Weisz, 2005; see also Barth et al, 2012;Weisz et al, 2012). Kolko et al (2012) suggested two new directions in research in child protection on the basis of previous research in psychology.…”
Section: Evidence-based Practice (Ebp)mentioning
confidence: 99%